THE EFFECT OF WORKLOAD AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE OF PT JASAMARGA KUALANAMU – TEBING TINGGI ROUTE - Putri Agustini Lubis; Rahmah Aina Az Zahra; Eka Mayastika Sinaga; Willy Cahyadi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to determine how the workload and work motivation affect the performance of employees of PT Jasamarga Segment Kualanamu - Tebing Tinggi both partially and simultaneously. The approach of this study is associative. The population is all employees of PT Jasamarga Segment Kualanamu - Tebing Tinggi and the sample is 35 employees of PT Jasamarga Segment Kualanamu - Tebing Tinggi. The data collection technique in this study uses a questionnaire technique. The data analysis technique in this study uses Multiple Linear Regression Analysis Test, Hypothesis Test (t Test and F Test), and Coefficient of Determination. Data processing in this study uses SPSS (Statistical Package for the Social Sciences) software version 29.00. Partially there is a positive and significant effect between workload on employee performance of PT Jasamarga Segment Kualanamu - Tebing Tinggi. Partially there is a positive and significant effect between work motivation on employee performance of PT Jasamarga Segment Kualanamu - Tebing Tinggi. Simultaneously there is a positive and significant effect between workload and work motivation on employee performance of PT Jasamarga Segment Kualanamu - Tebing Tinggi.